ANALISIS PERMASALAHAN PADA MATA PELAJARAN IPA DI KELAS V SDN KRAMAT JATI 18 PAGI - Safitri, Anita Yulia; Febriana, Alvira; Sa'adah, Sipa'us; Putri, Marsha Atika (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The purpose of this research is to find out the various problems faced by grade V students of SDN Kramat Jati 18 Pagi when learning the subject of Natural Science (IPA). Science lessons in elementary school have unique difficulties, especially because the topics include abstract ideas that may be difficult for students to understand at their stage of cognitive development. In order to collect relevant data for this study, in-depth interviews with grade V teachers, student learning motivation questionnaires, and direct observation techniques of the learning process were used as qualitative methodologies. The findings of this study highlighted some of the main challenges that grade V students face when learning science, such as the lack of laboratory space that can be used to support experiments and other experimental activities, as well as the lack of time, which often hinders more in-depth practical activities. Grade V teachers also mentioned how difficult it is to explain abstract concepts to children without using appropriate artifacts. Teachers try to overcome this challenge by using contextualized learning strategies, which relate science content to students' daily experiences. In addition, project-based learning (PjBL) methodology was used to help students understand the material by giving them easy projects that help make abstract ideas more understandable and tangible. According to the research findings, PjBL and contextual techniques successfully improved students' understanding and enthusiasm towards science lessons. It is hoped that the results of this study can help educators and school administrators to create more effective plans and materials to improve science teaching in elementary schools.